Recombinant pyruvate phosphate dikinase (rPPDK): development of antibody and antigen rapid dipstick tests for amoebiasis and identification of potential antiamoebic compounds - Syazwan Saidin (Tanjong Malim, 2017)
Recombinant pyruvate phosphate dikinase (rPPDK): development of antibody and antigen rapid dipstick tests for amoebiasis and identification of potential antiamoebic compounds by Syazwan Saidin